2002
DOI: 10.1177/088307380201700505
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Autonomic Nervous System Function in Patients With Breath-Holding Spells Treated With Iron

Abstract: To evaluate the autonomic nervous system of patients with breath-holding spells after iron treatment, we attempted to determine whether a dysregulation of the autonomic nervous system reflexes exists in children with severe cyanotic breathholding spells. An electrocardiogram for each subject was recorded for 24 hours in the subject's home and parasympathetic activity was investigated by the fast Fourier transform method. Hematologic data and clinical symptoms of all three patients treated with iron improved an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…It could be speculated that decreased oxygen carrying capacity due to iron deficiency may affect myocardial oxygenation, causing prolonged sinus recovery and longer sinus pauses. It was previously demonstrated that supplemental iron was effective in improving the dysregulation of autonomic nervous system reflexes 21.…”
Section: Discussionmentioning
confidence: 99%
“…It could be speculated that decreased oxygen carrying capacity due to iron deficiency may affect myocardial oxygenation, causing prolonged sinus recovery and longer sinus pauses. It was previously demonstrated that supplemental iron was effective in improving the dysregulation of autonomic nervous system reflexes 21.…”
Section: Discussionmentioning
confidence: 99%
“…Even if arising earlier than its 24‐month mean age of onset, BH will still typically persist beyond 2 years of age. This was seen in our control group, despite several months of iron supplementation – a proposed treatment for BH events – by the control subjects’ neurologist (Orii et al. , 2002).…”
Section: Discussionmentioning
confidence: 68%
“…The pathophysiological mechanisms of BHS remain controversial. The presence of an underlying dysfunctional autonomic nervous system with cerebral anoxia or cerebral ischemia resulting from vagus mediated cardiac arrest may be responsible for the condition [3][4][5][6]. The maturation delay in myelination of the brainstem could be the cause of breath-holding spells in children [7].…”
Section: Discussionmentioning
confidence: 99%